Customer benefits of demand-side management in the Nordic electricity market - Parkkonen, Olli (2016)
The increasing share of renewable energy sources is likely to lead to price effects in Nordic electricity market, resulting especially in increased volatility of spot and imbalance prices. The greater price volatility and amount of required balancing power increase the need for Demand-Side Management (DSM) in the electricity market and may as well increase the financial benefits of DSM participants. In this research I study the DSM in electricity mar-ket and evaluate how large the financial benefits of DSM participants could be. Monte Carlo simulation method is used to simulate imbalance prices with different volatilities for Finland and Sweden. The results show that increasing volatility may in some cases lead to substantial cost savings and additional revenues for the DSM participants. The revenues are higher in Finland compared to Sweden due to higher volatility of prices in the Finnish balancing power market. Lower threshold price (i.e. the lower opportunity cost of shifting or adjusting electricity demand) and higher flexible load capacity will in-crease the revenue obtainable from the DSM participation. However, there is a feedback effect, since the more DSM programs there are in the market, the less volatile the prices are likely to be. The magnitude of this effect, as well as that of the rebound effect (i.e. increased demand due to lower prices), is hard to quantify. If these feedback effects are large, cost savings and additional revenues for the DSM participants may be considerably smaller than what is documented in this study. I also discuss other limitations of the study.